2021
DOI: 10.1080/03610470.2021.1937461
|View full text |Cite
|
Sign up to set email alerts
|

Unfilterable Beer Haze Part II: Identifying Suspect Cell Wall Proteins

Abstract: The use of various diagnostic techniques has been previously utilized in the assessment of a commercially available India Pale Ale with cases of sporadically occurring unfilterable haze. The results from Part 1 suggested that β-glucans and proteins were the cause of the unfilterable haze and it was postulated that cell wall mannoproteins may also be a culprit of the unfilterable beer haze. In this follow-up study, proteins from high haze and low haze beer samples were precipitated and assessed using SDS-PAGE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Polyphenols, sugars and reducing substances, bitter resins, etc., accompanying protein substances play the role of accompanying compounds in the formation of a colloidal structure, supporting the spatial structure of protein molecules, the so-called “buffering capacity” both with respect to foam proteins and other protein structures [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols, sugars and reducing substances, bitter resins, etc., accompanying protein substances play the role of accompanying compounds in the formation of a colloidal structure, supporting the spatial structure of protein molecules, the so-called “buffering capacity” both with respect to foam proteins and other protein structures [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…The content of mannose polymers, expressed as mannan, for beer was at the level of 120–180 mg/L and is a consequence of the use of grain raw materials and microorganisms in the process [ 80 ]. Mannans in the structure of beer can be linked with proteins and represent compounds of yeast cells—mannoproteins involved in the haze formation [ 81 ].…”
Section: The Beer’s “Body” Biomoleculesmentioning
confidence: 99%
“…Huismann et al [ 139 , 140 ] found in unfilterable dry-hopped India Pale Ale, that the haze was caused by β-glucans and proteins. The authors suggested that this type of haze was due to the presence of unfilterable yeast cell wall mannoproteins in the beer.…”
Section: Problemsmentioning
confidence: 99%
“…A proteomics based study of commercial India Pale Ale diagnosed that overall protein and β‐glucan content were associated with this haze, and postulated that cell wall mannoproteins secreted by yeast were the primary cause [56]. A follow‐up study used protein fractionation, SDS‐PAGE and LC‐MS to reveal that both yeast cell wall mannoproteins and flocculins Flo1 and Flo9 were the most abundant proteins associated with unfilterable haze, providing avenues for future research to avoid problematic haze formation [57].…”
Section: Proteomics For Beer and Winementioning
confidence: 99%